The recruitment and ogranisation [i.e. organisation] of African labour for the Kimberley diamond mines: 1871-1888 - Siebörger, Robert Frederick (Rhodes University, Faculty of Humanities, Department of History, 1975)
Behind the fortunes in diamonds, the great open mines and the teeming town that was early Kimberley, were African labourers. Diggers seemed scarcely to care about them unless they were "in short supply", and many historians have been interested only in the guns they carried home with them. This study is concerned with these men: where they came from, why and how they came, and their treatment while they worked in Kimberley. The initial inspiration for the study came from the chapter on diamond production in Sheila van der Horst's Native Labour in South Africa, a remarkable contribution to the history of the Diamond Fields. The later studies by G.V. Doxey and more recently by John Smalberger which have expanded on aspects of Van der Horst's work, have led me to delve more deeply into other areas upon which they have not touched. One potentially fruitful line of study which was beyond the scope of this work was an investigation into the degree to which the Griqualand West labour question affected the attempts at South African federation in the 1870's. The main sources for the work have been the Griqualand West archives in the Cape Archives, for the period 1872-1880, and the various Kimberley newspapers. Labour returns were printed monthly in the Griqualand West Government Gazette for most years, till 1880. Cape Blue Books were useful sources for the period after 1880. De Beers Consolidated Mines Ltd. hold very little material relating to the pre-amalgamation period, though the extant minute books of the De Beers and Kimberley Central Diamond Mining Companies provided valuable information. A considerable number of contemporary published works were also consulted but, though most made some reference to African labour, few contained anything worthy of mention.
Keywords: Diamond mines and mining -- South Africa -- Kimberley; Unskilled labor -- Recruiting -- South Africa; Unskilled labor -- South Africa -- Kimberley -- Social conditions